(untitled) (Research, Society and Development, 2021)
This study aims to explore the sustainable practices carried out by organizations from different sectors in the last three years (2018-2021). Therefore, a systematic review was carried out, considering specific inclusion and exclusion criteria so that the most relevant studies could be selected for the discussion of the topic in question. 17 publications were selected to compose this study, most of the publications on sustainable practices in organizations came from Masters (Dissertations) (65%), with the years 2018 and 2019 with the highest number of publications, only one in 2020. In Regarding educational institutions and courses, there was no greater specific production, although the University of São Paulo (USP) has a greater number of publications. The results showed that the practices differ considering each sector in which the companies operate, which shows the influence of the market. Corporate reputation has been identified as one of the main motivations for adopting these practices. At the end of the study, it was found as sustainable practices, it was found that most of them have been preventive, of long-term application that also generate economic results for companies such as energy savings, water reuse, mitigation of solid waste generation, in addition to social practices being verified in the community in which the companies are inserted. The main motivation was the improvement of corporate reputation.